PROBLEMS OF EVALUATING VIDEO AND AUDIO RECORDINGS IN CIVIL AND ECONOMIC COURT PROCEEDINGS (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
In Uzbekisran, within the framework of the "smart city" project, video surveillance is currently being implemented in the intersections, public places, residential and commercial areas of our country's cities. Video surveillance is not only aimed at preventing and fighting crime, but these video recordings can serve as an important source of evidence in economic and civil disputes. The Civil Procedural Code of the Republic of Uzbekistan, adopted in a new version, is also significant in that it includes modern information technologies in the Economic Procedural Codes of the Republic of Uzbekistan. In particular, in the chapter of the Civil Procedure Code of the Republic of Uzbekistan on court proceedings, norms are defined for replaying audio or video recordings and their verification.